If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b + 11 + -36 = 2b + 2 Reorder the terms: 11 + -36 + 8b = 2b + 2 Combine like terms: 11 + -36 = -25 -25 + 8b = 2b + 2 Reorder the terms: -25 + 8b = 2 + 2b Solving -25 + 8b = 2 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. -25 + 8b + -2b = 2 + 2b + -2b Combine like terms: 8b + -2b = 6b -25 + 6b = 2 + 2b + -2b Combine like terms: 2b + -2b = 0 -25 + 6b = 2 + 0 -25 + 6b = 2 Add '25' to each side of the equation. -25 + 25 + 6b = 2 + 25 Combine like terms: -25 + 25 = 0 0 + 6b = 2 + 25 6b = 2 + 25 Combine like terms: 2 + 25 = 27 6b = 27 Divide each side by '6'. b = 4.5 Simplifying b = 4.5
| 16f-24=16f-32 | | 3x+5=-2x-10whatsx | | 6u-(2u-4)7=3 | | 6(16-4y)=72 | | 5(x-4)-4(x+1)=0 | | 10x-5=9x+8 | | (8x+2)(9x+3)+x=180 | | (8x+2)(9x+3)+x=q | | 5-.66666666n=7 | | 64-7x=11x+18 | | 2x+2=40 | | 8log(x+3)=10 | | 1-3x+8x=3+5x | | 4x+-2=6 | | -16y=0 | | 3(m-9)= | | 3x(x-12)=0 | | (x^2-x+.25)=(.3+x) | | 8-4(m+5)= | | X+2=3x+2-2x | | a^4-12a^2+35=0 | | 6a(2a-1)-(3a^2-3a)= | | -8x=4 | | n-15=30 | | -30-5m=-4(m+7) | | 8x^2-11x+3=0 | | 27=17-2y | | -2=2x+10 | | 26+4a=6a | | 35x^2+56x+21=0 | | 4s=76 | | 10x-3(x-6)=11+30 |